EQUIVALENCE OF TWO FORCES FROM DIFFERENT POSITIONS THAT PRODUCE THE SAME AMOUNT OF VIBRATION - Giovanni, Brian
Rotating machines are commonly used for industrial purpose. This type of machines always produces vibration during operation. The vibration produced is typically caused by a dynamic force from an unknown location. To pinpoint the location of the source, a basic understanding of force equivalence is needed. The lack of knowledge about force equivalence may lead to misleading vibration sources. Hence, this research aims to learn about two force equivalence from different positions that produce the same vibration amplitude at a vibration measurement point. This research began by performing state-space simulation to choose the most representative equivalent viscous damping models towards the actual system under studied. The research continued by estimating dynamic parameter values (mass, spring stiffness, viscous damping constant) of the test apparatus. Furthermore, these dynamic parameter values are used in the force equivalence equation that has been derived to obtain the force equivalence curve. Based on this curve, a state-space simulation is performed to prove that the derived equation matches the simulation results. The research continued by performing force equivalence test using an impact hammer. On this test, force equivalence curve can be obtained by dividing two different FRF (Frequency Response Function) curves. From the test being conducted, this division produces a similar force equivalence graph with that obtained theoretically.